Drivers and consequences of archetypical shifting cultivation transitions. Issue 2 (24th January 2023) - Martin, Dominic A.; Llopis, Jorge C.; Raveloaritiana, Estelle; Coomes, Oliver T.; Andriamihaja, O. Ravaka; Bruun, Thilde Bech; Heinimann, Andreas; Mertz, Ole; Rakotonarivo, O. Sarobidy; Zaehringer, Julie G.
Abstract: Shifting cultivation remains an important land system in many tropical landscapes, but transitions away from shifting cultivation are increasingly common. So far, our knowledge on the social–economic and environmental drivers and consequences of such shifting cultivation transitions is incomplete, focusing on certain transitions, drivers, consequences or regions. Here, we use an archetype approach, validated through systematically identified literature, to describe eight archetypes encompassing the transitions from shifting cultivation to (1) perennial plantation crops, (2) permanent agroforestry, (3) regrown secondary forest, (4) permanent non‐perennial crops, (5) pasture, (6) wood plantation, (7) non‐cultivated non‐forested land and (8) restored secondary forest (ordered in decreasing prevalence). We then discuss social–economic and environmental factors favouring and disfavouring each archetype. This reveals that higher expected land rents, resulting from increased market access, crop price surges, secure land tenure and state interventions, are the main drivers of archetypical transitions to perennial plantation crops, permanent agroforestry, permanent non‐perennial crops and wood plantation. The prioritisation of other activities, both on‐ and off‐farm, favours transitions to regrown secondary forest and non‐cultivated non‐forested land, depending on plot‐level environmental conditions. Active forest restoration is typically implemented through state or NGO interventions. Turning to the consequences of archetypical transitions for biodiversity, the environment and livelihoods, we find that positive environmental outcomes prevail for transitions to permanent agroforestry, regrown secondary forest and restored secondary forest. Negative environmental outcomes dominate for four typically economically profitable transitions to perennial plantation crops, permanent non‐perennial crops, pasture and wood plantation. Non‐income‐related social–economic outcomes are heterogeneous within all archetypes and highly context‐dependent. Our archetype analysis shows that shifting cultivation transitions are diverse in themselves, in their drivers and their consequences. This calls for a critical and contextualised appraisal of the continuation of shifting cultivation, as well as the transition away from it, when designing land system policies that work for people and nature. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.